Taxonomical, morphological, ecological and chorological notes on Oxybasis chenopodioides and O. rubra (Chenopodiaceae) in Italy - Iamonico, Duilio (Hacquetia, 2015)
On the basis of floristic surveys, examination of herbarium specimens and review of literature, notes on the taxonomy, morphology, and ecological features are given of Oxybasis chenopodioides and morphologically fairly similar Oxybasis rubra. Their distributions in Italy according to Provinces are discussed and mapped.